Overweight and Obesity Based on Four Reference Systems in 18, 382 Paediatric Patients with Type 1 Diabetes from Germany and Austria. (1st June 2015) - Flechtner-Mors, M.; Schwab, K. O.; Fröhlich-Reiterer, E. E.; Kapellen, T. M.; Meissner, T.; Rosenbauer, J.; Stachow, R.; Holl, R. W.
Abstract : Aim . To evaluate the prevalence of overweight and obesity in paediatric type 1 diabetes (T1D) subjects, based on four commonly used reference populations. Methods . Using WHO, IOTF, AGA (German pediatric obesity), and KiGGS (German Health Interview and Examination Survey for Children and Adolescents) reference populations, prevalence of overweight (≥90th percentile) and obesity (≥97th percentile) and time trend between 2000 ( n = 9, 461) and 2013 ( n = 18, 382) were determined in 2–18-year-old T1D patients documented in the German/Austrian DPV database. Results . In 2000, the overweight prevalence was the highest according to IOTF (22.3%), followed by WHO (20.8%), AGA (15.5%), and KiGGS (9.4%). The respective rates in 2013 were IOTF (24.8%), WHO (22.9%), AGA (18.2%), and KiGGS (11.7%). Obesity prevalence in 2000 was the highest according to WHO (7.9%), followed by AGA (4.5%), IOTF (3.1%), and KiGGS (1.8%). In 2013, the respective rates were WHO (9.6%), AGA (6.2%), IOTF (4.5%), and KiGGS (2.6%). Overall, the prevalence of overweight and obesity increased from 2000 to 2006 ( p < 0.001) but showed stabilization thereafter in girls and overweight in boys. Conclusion . Overweight and obesity prevalence in T1D subjects differs significantly if it is assessed by four separate reference populations. More detailed assessment of each child is required to determine obesity-related risks.